Pengaruh Penggunaan Pupuk Bersubsidi terhadap Efektivitas Petani di Kelompok Tani Tosalamae Kabupaten Pinrang - Rais, Muh; Yusriadi, Yusriadi; Nurhaedah, Nurhaedah (LaGeografia, 2021)
The purpose of this study is to find out the influence of the use of subsidized fertilizer on the effectiveness of farmers based on the right indicators of price, right amount, on time, right place, and the right type in the farmer group tosalamae. This research is descriptive quantitative. The method of data retrieval used is observation, questionnaire and interview. The method of data analysis used is multiple linear regression. Primary data comes from farmer interviews and secondary data comes from research-related agencies. The results showed that on time is a real effect on (Y) the effectiveness of the use of subsidized fertilizers because of the significance (Sig) below alpha (α) 0.05 ie 0.016 means a real effect on the use of subdivided fertilizers in farmer groups tosalamae. Subsidized fertilizer is very important for farmers in the process of farming, so when farmers want to use subsidized fertilizer is always available in the time farmers need it. Therefore, on time it is very important in the use of subsidized fertilizers.